Chapter 13 Stalinism, War, and Artistic Representation of Reality Konstantin Simonov's Critique of the 'System of Silence' in 1956 - Ikonen, Susan (Taylor & Francis, 2023)
This chapter analyses Konstantin Simonov's thought from the largely understudied point of view of de-Stalinization. Simonov showed already in 1956 how the representation of the Great Patriotic war was tightly intertwined with the personality cult of Stalin, and how this entanglement had caused literature and art either to portray Soviet reality in a distorted manner or to keep silent about social difficulties. By criticizing key authoritative documents of the early post-war years, Simonov revealed how Stalin's wish to forge the image of the Great Patriotic war resulted in the widespread tendency of embellishing reality in Soviet literature and art. The chapter also tracks how the Party rebuked Simonov's claims without mentioning him as the initiator of the ideas. The chapter thus testifies to some of the problems of 'de-Stalinization' and how some of its key issues could not be openly discussed in the Soviet Union until the late 1980s. The chapter is based on previously untapped archival material, and it contributes to the scholarly discussion of the thaw-era de-Stalinization, Simonov's roles within the Soviet literary establishment, and questions of the representation of reality in Soviet art in general and the representation of the Great Patriotic war in particular.